The Procedural Law of State Administrative Courts As The Rule of Adjudication: Exploring Hart’s Theory - Efendi, Aan; Sudarsono (Universitas Brawijaya, 2024)
In Hart’s theory, law is a combination of two types of rules: primary and secondary. Primary rules regulate the behavior of individuals or institutions, while secondary rules relate to primary rules, including the rule of recognition to identify the primary rules, the rule of change to modify primary rules, and the rule of adjudication to address violations of primary rules. The law of administrative procedure is an adjudication regulation that resolves violations of primary rules governing the behavior of government organs in administering government. Using a doctrinal legal method, this study explores two problems: the rule of adjudication in Hart’s theory and the procedural law of administrative courts understood as the rule of adjudication according to Hart’s theory. The study results reveal that, first, in Hart’s theory, the rule of adjudication does not stand alone but is, instead, attached to the primary rules, which function to identify violations, adjudicate, and provide punishment or compensation for violations of the primary rules; second, based on Hart’s theory, the procedural law of administrative courts serves as a rule of adjudication for the adjudication process dealing with violations of primary regulations regarding the obligations of government organs in administering government which must be guided by legislation and the general principles of good governance.